ARTISTIC INTERPRETATION OF THE IMAGE OF THE CREATOR IN A LITERARY WORK (International journal of artificial intelligence, 2025)
This article is devoted to the analysis of the artistic interpretation of the image of the creator in literary studies. It examines how the writer’s imagination, inner world, personal experiences, and psychological states are reflected in the process of creating a literary work, as well as how the image of the creator is transformed into an artistic form through creative thinking.